CORRELATION BETWEEN S.T.O.N.E NEPHROLITHOMETRY SCORING IN PREDICTING FREE-STONE RATE AFTER PERCUTANEOUS NEPHROLITHOTOMY - putri, Karinda triharyu caesari; Djojodimejo, Tarmono; Rizaldi, Fikri; Hardjowijoto, Sunaryo (Indonesian Journal of Urology, 2017)
Objective: To investigate free-stone rate after Percutaneous Nephrolithotomy (PNL) using S.T.O.N.E nephrolitometry scoring system, with regards of stone size (S), skin-to-stone distance (T), obstruction degree (O), number of calyx involved (N), and stone density (E) in Non Contrast CT Scan (NCCT). Material & methods: This is an analytic observational study on patients with renal stones undergoing PNL. All patients underwent NCCT before and after PNL; each variables was measured and counted for a total score. Post-operative evaluation was done using NCCT. Results: Thirty patients met inclusion criteria, 19 (63.3%) were stone-free, and 11 (36.7%) were with residual stone. Among the five variables, stone size (p=0.005), number of calyx involved (p=0.002) affected the outcome of surgery, while skin-to-stone distance, obstruction degree, and stone density did not. The overall total score of S.T.O.N.E nephrolithometry is correlated with the outcome of PNL (p=0.001). Conclusion: S.T.O.N.E nephrolithometry is a simple scoring system, while it is also easy to use, and can be used to predict the free-stone rate after PNL.